A Lightweight Genetic Based Algorithm for Data Security in Wireless Body Area Networks - Jabeen, Tallat; Ashraf, Humaira; Khatoon, Asma; Band, Shahab S.; Mosavi, Amir (IEEE access, 2020)
The new generation of wireless body area networks (WBAN) for the internet of things (IoT) is emerging in a fast-paced. Today patients can be tested using remote clinical nanosensors. WBAN involves small interconnected sensors for the collection of ongoing medical data and transmitted through the networks for further processing. However, the protection of healthcare data is very important and difficult because of the various active and passive numbers of attacks. Although there exist several literatures on data security techniques such as digital signatures, Elliptic curve cryptography, and Advanced Encryption Standards (AES) they contain stumbling blocks for the security methodologies. Thus, in this paper, a novel data protection genetic-based encryption scheme is proposed for higher performance.